The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/star.19890410205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage on Starch Content and Modification of Cassava Starch

Abstract: The effect of storage on yield and modification of starch using hydrochloric acid and acetic anhydride were studied. Yield of starch from fresh roots (24.4%) was significantly greater than yield (16,2%) from roots stored at room temperature for six days. On a dry weight basis the amount of starch in the roots decreased over a six day storage period. The proximate composition of cassava starch on dry weight basis was 0.24% ash, 0.13% fat, 0.49% protein, 0.15% crude fibre and 98.4% starch. The isolated starch wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 9 publications
(2 reference statements)
4
53
0
Order By: Relevance
“…The LGC of the acid hydrolysed and low-citric acid substituted starches improved from 4% (native) to 2% (Table 2) across cultivars, except for bitter yam starch. Acid hydrolysed hybrid maize starch, corn starch, potato, rice, red bean and cassava starches showed improved gelling capacity over their unmodified counterparts Wang and Wang 2001;Osunsami et al 1989;Kim and Ahn 1996). In our study, native and tempered starches developed soft viscous gels at lower concentrations (2-4% w/v), which became progressively hard or very hard as concentration increased (10-20% w/v), while acid hydrolysis and low-citric acid-substitution enhanced formation of hard gels at the different concentrations (2-20% w/v) in all cultivars.…”
Section: Least Gel Formation Concentration (Lgc) Of Native and Modifimentioning
confidence: 96%
“…The LGC of the acid hydrolysed and low-citric acid substituted starches improved from 4% (native) to 2% (Table 2) across cultivars, except for bitter yam starch. Acid hydrolysed hybrid maize starch, corn starch, potato, rice, red bean and cassava starches showed improved gelling capacity over their unmodified counterparts Wang and Wang 2001;Osunsami et al 1989;Kim and Ahn 1996). In our study, native and tempered starches developed soft viscous gels at lower concentrations (2-4% w/v), which became progressively hard or very hard as concentration increased (10-20% w/v), while acid hydrolysis and low-citric acid-substitution enhanced formation of hard gels at the different concentrations (2-20% w/v) in all cultivars.…”
Section: Least Gel Formation Concentration (Lgc) Of Native and Modifimentioning
confidence: 96%
“…The retrogradation rate of acid-thinned starch gels increased as hydrolysis proceeded (Kang et al 1997). Acid modification increased solubility and gel strength and decreased the viscosity of starches (Kim and Ahn 1996;Osunsam et al 1989). According to Wang and Wang (2001), the behavior of acid-thinned starches is associated with the average chain length polymerization degree (PD).…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 97%
“…4). According to diverse researchers, acid thinning increased the solubility of starches (Whistler and Daniels 1990;Kim and Ahn 1996;Osunsam et al 1989;Sandhu et al 2007). Kim and Ahn (1996) reported an increase in the solubility of red bean maize starches hydrolyzed with acid, attributed to the damaged structures of starch granules.…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 97%
“…Chromatographic analysis showed that amylose and amylopectin was prepared by reacting starch with acetic anhydride in an alkaline849 solution. The acetylation increased the water solubility and paste clarity, decreased the 850 pasting viscosities and gelling ability, the glass transition and gelatinization temperatures, and851 improved the freeze-thaw stability(Aiyeleye, Akingbala, & Oguntimein, 1993; Agboola, 852 Akingbala, & Oguntimein, 1991a & 1991b;Moorthy, 1985;Osunsami et al, 1989). Dynamic 853 moduli (G' and G'') of starch paste (5%) were higher or lower than control, depending on the 854 specific starch genotypes used(Osundahunsi & Mueller, 2011).…”
mentioning
confidence: 94%